Wood under fresh water: Effect on the chemical properties and on decay resistance - Tainise V. Lourençon; Patrícia S. B. dos Santos; Jalel Labidi; Darci A. Gatto; Margarete R. F. Gonçalves (Maderas: Ciencia y Tecnología, 2016)
This study aimed to evaluate the effect of waterlogging on the chemical properties and on decay resistance of two fast-growing eucalypt species. Samples of spotted gum and rose gum wood were placed underwater and taken out at different times: after 4, 8 and 12 months. Chemical properties were performed via wet chemical quantification (Tappi standards), monomeric sugars by HPLC, and qualitative evaluation of extractives by Py-GC/MS and ATR-IR spectroscopy; biological performance was investigated using Trametes versicolor and Gloeophyllum trabeum rot fungi. The results showed slight changes to the chemical properties of both wood species, with an increase in lignin represented by the reduction of sugars due to waterlogging. Both species showed higher susceptibility to Gloeophyllum trabeum mainly in the sapwood, with no influence on decay resistance due the waterlogging.